Relationship between physical environment, behavioral environment and individual workspace towards workplace satisfaction / Nor Hisham Mohammad... [et.al] - Mohammad, Nor Hisham; Ibrahim, Muhammad Nor Shafiee; Rambli, Nasser (2015)
The workplace environment plays an important role for the employees. Nowadays, employees may have a large number working alternatives. Therefore, the environment in workplace become a crucial factor for accepting and/or keeping or secured the jobs. The objectives of this study are to examine the relationship physical environment, behavioural environment and individual workspace towards workplace satisfaction. As a cooperative bank in Malaysia, Bank Rakyat very well known on sharia practice that recognized globally. In the past, office layout was designed mainly that suits service provider and security aspect. The trend has change rapidly. Without compromising the security aspects, modem corporate organization including Bank Rakyat emphasis more on utilizing their workplace designed as part as their corporate image building, applying user friendly layout, design uniformity and continuously improved efficiency and effectiveness of the bank operation. Utilizing the survey approach, this study consisted of 129 respondents from Bank Rakyat in Kuching. This quantitative study applied a questionnaire as a main research instrument. The analysis is concentrated on the relationship independent variables which are physical environment, behavioural environment and individual workspace while the dependent variable is workplace satisfaction. It depends on various elements of workplace design. The result shows that all variables have statistically significant relationship. This research can be a base of future reference for Bank Rakyat towards understanding their employee’s needs and customers’ services.